Lower Lid Ectropion in Hypohidrotic Ectodermal Dysplasia - Xiaoyun Zhang; Li Xu; Xiaofang Li; Chunyan Li; Haitao Zhang (Case Reports in Ophthalmological Medicine)
We report a case of a lower lid ectropion with ectodermal dysplasia and ectropion blepharoplasty surgery experience. A 14-year-old Han nationality male patient with typical characteristics of hypohidrotic ectodermal dysplasia presented to our clinic for his right lower lid eversion. The patient was diagnosed as having hypohidrotic ectodermal dysplasia and underwent an uneventful blepharoplasty surgery. The lower lid maintained normal position during the 10-month follow-up period. Patients with ectodermal dysplasia could firstly visit ophthalmologist for their ectropion and blepharoplasty surgery could be useful for the disease.